Consumer preference analysis of organic food in Terengganu / Siti Nor Hidayah Abdullah Zawawi ... [et al.] - Abdullah Zawawi, Siti Nor Hidayah; Fakih, Puteri Nur Suraya; Muhammad Ghazali, Ameleya; Zulkurnain, Muhammad Zulhilmi (2023)
The organic food industry is expanding in Malaysia, as demand has risen as consumers become more knowledgeable about the advantages of eating organic food. However, the organic product in Malaysia is still limited in production, as most of the organic products are imported from other countries. This research is to study the factors that influence the consumer preference in buying the organic food in Terengganu. Therefore, this study aims to examine the effect of attitude, subjective norms, and health consciousness towards consumer intention to buy organic food. The study employed the Statistical Package for the Social Sciences (SPSS) and SmartPLS 4.0: PLS-SEM to assess the 397 respondents gathered through an online questionnaire. The analysis revealed causal relationships among the proposed variables, highlighting the quantitative research focus of this study. This study revealed that three independent variables which are subjective norm were not physically affect the customer’s intention to purchase organic food, meanwhile attitude and health consciousness are significant influences towards customer’s intention to purchase. The study is expected to increase knowledge about organic food for future studies in the field of organic food to provide them with a better understanding of consumers' preferences in purchasing organic food. Besides, the findings are beneficial to improve consumer’s quality of life as well as to influence policymakers to execute effective programs to achieve a healthy lifestyle among adults in Malaysia by consuming organic food.